2022
DOI: 10.1002/hbm.25828
|View full text |Cite
|
Sign up to set email alerts
|

Meta‐analytic evidence for downregulation of the amygdala during working memory maintenance

Abstract: The amygdala is a region critically implicated in affective processes. Downregulation of the amygdala is one of the hallmarks of successful emotion regulation. Top-down inhibition of the amygdala is thought to involve activation of the executive control network. This reciprocal relationship, however, is not exclusive to explicit emotion regulation. It has been noted that any cognitively demanding task that activates executive control network may downregulate the amygdala, including a standard working memory ta… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 66 publications
1
6
0
Order By: Relevance
“…Second, dlPFC and dACC were found to have densely reciprocal connections with the amygdala 63 . The feedback inhibition from dlPFC and dACC to amygdala align with earlier findings, as these regions are thought to downregulate the amygdala not only during explicit emotion regulation but also during cognitively demanding tasks 64,65 . The context-dependent interaction of amygdala with prefrontal regions in video-watching behaviors might arise from the differentiated projections from the positive- and negative-encoding neurons in amygdala 66 , but circuitry level evidence is required to test this conjecture.…”
Section: Discussionsupporting
confidence: 87%
“…Second, dlPFC and dACC were found to have densely reciprocal connections with the amygdala 63 . The feedback inhibition from dlPFC and dACC to amygdala align with earlier findings, as these regions are thought to downregulate the amygdala not only during explicit emotion regulation but also during cognitively demanding tasks 64,65 . The context-dependent interaction of amygdala with prefrontal regions in video-watching behaviors might arise from the differentiated projections from the positive- and negative-encoding neurons in amygdala 66 , but circuitry level evidence is required to test this conjecture.…”
Section: Discussionsupporting
confidence: 87%
“…On the one hand, we suggest that the current results may be a consequence of competition between salience/defensive neural networks and central-executive networks. In our study, adaptive WMT was a cognitively demanding activity, and performing this task resulted in increased activation of the central-executive network (de Voogd & Hermans, 2022). Correspondingly, the activation of salience/defensive neural networks involved in the amygdala is diminished, which may lead to a general improvement in ER.…”
Section: Discussionmentioning
confidence: 82%
“…An increase in DLPFC activity has been shown to facilitate emotion regulation and improve cognitive control (Chen, Oei et al 2023), and impaired emotional regulation due to DLPFC dysfunction is closely related to depression, in which the complex interaction between cognition and emotion is significantly disrupted (Salehinejad, Ghanavai et al 2017). Previous studies have repeatedly shown a negative correlation between DLPFC and AMY (Davidson and Irwin 1999, Mayberg, Liotti et al 1999, Damasio, Grabowski et al 2000, demonstrating top-down control of emotion through increased DLPFC recruitment (Bishop 2008, Iordan, Dolcos et al 2013) to down-regulate activity in AMY (Loos, Schicktanz et al 2020, de Voogd andHermans 2022).…”
Section: Discussionmentioning
confidence: 99%